Paving the Way for Climate Neutral and Resilient Historic Districts [version 1; peer review: 1 approved, 2 approved with reservations] - Aitziber Egusquiza; Saioa Zorita; Daniel Lückerath; Gemma Garcia; Sophia Silverton; Alessandra Bonazza; Emilio Servera; Antonis Kalis; Igone Garcia (Open Research Europe, 2023)
Climate change is a major global threat to our society’s urban areas, with the majority of Europe's population living in cities and their cultural heritage. Historic districts of significant cultural value and the communities connected to these places have an important role to play in fostering location-based identity and economy, social cohesion, innovation, urban regeneration, and climate change adaptation. Thus, it is important to make historic districts climate resilient, by jointly considering climate change adaptation, disaster risk management, heritage management, and sustainable urban development. However, this is often a major challenge for local and regional administrators and relevant stakeholders. This paper constitutes the first major result of the EU R&I Task Force for Climate Neutral and Resilient Historic Urban Districts. It provides an overview of the challenges faced by practitioners and researchers when jointly addressing the needs of resilient historic districts and provides an initial set of recommendations produced by the task force to address these challenges. These challenges cover different issues around five topics (i) data availability, use and its management, (ii) the common responsibility fragmentation in policy and governance, (iii) the challenge on integrating local knowledge and traditions in resilience building, (iv) the difficulties around the co-ownership and co-production in governance and (v) the importance of mainstreaming heritage management in adaptation and resilience policies.